Urban Amenities – an Element of Public Dimension of Housing Stock - Sokołowicz, Mariusz E. (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The concept of urban amenities is an important but still not strongly expressed element of the discussion on the public dimension of housing. Amenities as a part of so called housing neighborhood are considered as public, because they form a source of externalities that affects the consumption utility of housing and urban living. In consequence, governing urban facilities can affect the efficiency of housing policy. From this point of view a key question is, which kind of amenities is considered as first and which as second‑tier by urban residents. Besides, in urban amenities studies, new approaches and tools identifying the interdependencies between housing stock and neighborhood, are implemented. The aim of this paper is an attempt to answer the question about the impact of urban amenities on the quality of housing stock. It attempts firstly to explain the notion of urban amenities, urban neighborhood effects, along with an identification of the key types and characteristics of these concepts. Secondly, it present the results of the study conducted in the city of Łódź, contributing to the identification of the scale of the impact of urban amenities on the level of living satisfaction reported by the respondents, as well as presenting the scale of the influence of these factors on the potential change of housing location. The results obtained are of an initial nature and may be the starting point for further in‑depth studies.